4 - Aetiological Explanations of Epilepsy and Implications on Treatments Options among Yoruba Traditional Healers in Southwest Nigeria: - Tosin Funmi Ademilokun; Ojo Melvin Agunbiade (African Sociological Review, 2021)
In Nigeria, traditional healers play major roles in the treatment of patients living with epilepsy and their status as well as worldview have a considerable influence on the therapies or treatments that are provided, thereby affecting the quality of care and rights of their clients. With the dearth of studies on these healers’ management of clients with epilepsy, this study explored their perspectives on the aetiology of epilepsy and how their view and understanding of the condition shape the treatments and therapies that are accessible to their clients. Semi- structured interviews were conducted with 24 traditional healers considered as experts in the treatment of epilepsy in two Yoruba communities in Southwest Nigeria. Findings showed these healers perceived epilepsy as a health condition that is highly stigmatised and fearfully avoided among the Yoruba people. A multicausal view was advanced in their aetiological explanations of the causes of epilepsy ranging from natural, hereditary, and the supernatural. Each epilepsy case requires clear divination to understand the underlying cause and possible regimen to adopt in providing help and recovery. Treatments are often in stages and mixed as the individual progresses towards recovery. Of all the aetiologies, epilepsy cases that are attributed to preternatural and supernatural forces were considered most difficult to treat. The paper concludes that with the traditional healers’ status in the community, and acceptance of their treatment modalities, the absorption of traditional medical practice will aid the supervision of their practice and help reduce exploitation and improve the quality of care.